الحماية الجزائية للبيئة في ضوء أحكام الشريعة الإسلامية والتشريع الجزائري - لقريد, سناء (University of eloued جامعة الوادي, 2015)
يتناول موضوع البحث الموسوم " بالحماية الجزائية للبيئة في ضوء أحكـام الشريعة الإسلامية والتشريع الجزائري" دراسة وتقييم مدى فاعلية الحماية الجنائية في مجال حماية البيئة، حيث يتعرض الفصل الأول مـن البحـث إلـى الإطـار المفاهيمي للدراسة ورعاية البيئة في الشريعة الإسلامية والتشريع الجزائري وذلك بالتطرق إلى مفهوم البيئة والتلوث والحماية الجزائية ثم بيان الرعاية التي أحاطها كلا التشريعان بالبيئة وكيفية حمايتها. أما الفصل الثاني من الدراسة يتعرض إلى إحصاء الجرائم التي تمس بالبيئة إلى جانب التعرض إلى العقوبات التي تضمن حماية البيئة من مصـادر الخطـرالمختلفة The subject of the research maked " the penal protection of the environement in the light of islamic law and algerian legislation" deals with the study and evaluation of the effectiveness of the criminal protection in the field of environmental protection. Where the first chapter of the research is exposed to the conceptual framework of the study and the care of the environment in the islamic law and algerian legislation and that by addressing the concept of the environment the pollution and the penal protection then to determine the care that shrouded both pieces of legislation to the environment and how to protect it. But the second chapter of the study is exposed to count crimes that affect the environment as well as exposure to the sanctions which ensures the protection of the environment from various sources of danger
شريعو وقانون
Keywords: الحماية الجزائية/البيئة/التشريع الجزائري; Criminal protection/Environment/Algerian legislation